The double movement & post‐Arab Spring consociationalism - Salamey, Imad (2016)
This article explores the theoretical proposition that the Arab Spring is a manifestation of globalization's double movement. On one hand, the global movement of economic and cultural liberalization has fundamentally deconstructed the functional order of centralized national state‐autocracy. On the other hand, globalization's economic, cultural and security integration has been counterbalanced by a movement for autonomous and communitarian protectionism. The latter is being extrapolated by the impact of a growing multipolar regional system and declining state nationalism. The post‐Arab Spring's Middle East and North African governing dilemma manifests this dialectic antagonism. The assertion of the double movement calls for the mutation of globalism and communitarianism within new governing arrangements. This article examines the potential emergence of irredentist power sharing typologies with a special focus on Lebanese consociationalism.